Associations between narrative transportation, risk perception and behaviour intentions following narrative messages about skin cancer. Issue 5 (4th May 2018) - Dillard, Amanda J.; Ferrer, Rebecca A.; Welch, Jessica D.
Abstract : Objective: Narrative messages may be an effective strategy to increase risk perceptions and motivate preventive behaviours related to cancer. The aim of this research was to examine associations between narrative transportation (i.e. psychological absorption into a narrative), risk perceptions, and intentions following narrative messages about skin cancer. Design: In two studies, women who reported indoor tanning read first-person narrative messages about skin cancer. We examined associations between narrative transportation and the women's responses to the narratives, including risk perceptions for skin cancer and behaviour intentions to reduce risk. Associations between transportation, knowledge and worry were also examined. Results: Greater transportation was associated with higher intentions to perform skin self-examination, talk to one's doctor about skin cancer, and look for more information. Greater transportation was also associated with higher gut feelings of risk and higher worry about skin cancer, but not deliberative risk perceptions or knowledge from the message. Additional analyses showed that after controlling for risk perception and worry, transportation had unique associations with some behaviour intentions. Conclusion: Findings suggest that narrative transportation may be an important component to the persuasion of cancer narratives. Future research should explore ideas such as the role of the experiential system in narratives' influence.